Transforming growth factor-β signalling: role and consequences of Smad linker region phosphorylation - Kamato, Danielle; Burch, Micah L.; Piva, Terence J.; Rezaei, Hossein B.; Rostam, Muhamad Ashraf; Xu, Suowen; Zheng, Wenhua; Little, Peter J.; Osman, Narin (Elsevier, 2013)
Transforming growth factor-β (TGF-β) is a secreted homodimeric protein that plays an important role in regulating various cellular responses including cell proliferation and differentiation, extracellular matrix production, embryonic development and apoptosis. Disruption of the TGF-β signalling pathway is associated with diverse disease states including cancer, renal and cardiac fibrosis and atherosclerosis. At the cell surface TGF-β complex consists of two type I and two type II transmembrane receptors (TβRI and TβRII respectively) which have serine/threonine kinase activity. Upon TGF-β engagement TβRII phosphorylates TβRI which in turn phosphorylates Smad2/3 on two serine residues at their C-terminus which enables binding to Smad4 to form heteromeric Smad complexes that enter the nucleus to initiate gene transcription including for extracellular matrix proteins. TGF-β signalling is also known to activate other serine/threonine kinase signalling that results in the phosphorylation of the linker region of Smad2. The Smad linker region is defined as the domain which lies between the MH1 and MH2 domains of a Smad protein. Serine/threonine kinases that are known to phosphorylate the Smad linker region include mitogen-activated protein kinases, extracellular-signal regulated kinase, Jun N-terminal kinase and p38 kinase, the tyrosine kinase Src, phosphatidylinositol 3′-kinase, cyclin-dependent kinases, rho-associated protein kinase, calcium calmodulin-dependent kinase and glycogen synthase kinase-3. This review will cover the role of Smad linker region phosphorylation downstream of TGF-β signalling in vascular cells. Key factors including the identification of the kinases that phosphorylate individual Smad residues, the upstream agents that activate these kinases, the cellular location of the phosphorylation event and the importance of the linker region in regulation and expression of genes induced by TGF-β are covered.